Patologia da vagina em ressonância magnética - Almeida, Joana Rebelo de; Cunha, Teresa Margarida (My University, 2012)
A ressonância magnética é um método excelente e cada vez é mais indicado na avaliação de alterações da vagina, em virtude da sua capacidade de avaliação multiplanar e alto contraste tecidual. A RM é usada no estadiamento de tumores da vagina e detecção de recidivas. Também é útil na caracterização de malformações congénitas. Neste artigo descrevemos as características em ressonância magnética das diferentes patologias congénitas e adquiridas da vagina.

Magnetic resonance imaging is an excellent modality for the characterization of vaginal pathology due to its multiplanar ability and superb contrast resolution. MRI has been used to stage vaginal malignancies and assist detection of recurrence. It has also proved useful in the characterization of Müllerian duct anomalies. In this article we review the typical imaging characteristics on MRI of congenital and acquired conditions involving the vagina.
Magnetic resonance imaging of vaginal pathology
Keywords: Malformações congénitas da vagina; Ressonância Magnética; Neoplasias da vagina; RM; Congenital anomalies of the vagina; Vaginal neoplasms; MRI